WORK-LIFE BALANCE THROUGH RELIGIOSITY AMONG ENTREPRENEURS IN MALAYSIA - Tee , Chun Wee (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Work-life balance (WLB) seeks to balance professional and personal domains to sustain overall well-being, yet the issue remains unresolved despite decades of attention. Most studies have emphasized organizational flexibility, psychological approaches, and technical solutions, reflecting perspectives rooted in Western contexts. Despite growing interest in WLB research in Asia, the role of religiosity in shaping WLB remains insufficiently examined. In Malaysia, entrepreneurship is central to economic development, yet limited research explores how entrepreneurs draw upon religious values to manage work-life conflict. The objective of this study is to investigate how the spiritual coping framework in religiosity to influences entrepreneurs’ strategies for achieving WLB in Malaysia. A qualitative case study design is adopted. Semi-structured interviews with 10–20 entrepreneurs from diverse religious backgrounds—including Islam, Christianity, Buddhism, and Hinduism—will be conducted. Data will be analysed using thematic coding to identify patterns and mechanisms through which religiosity supports WLB. Key expected findings include evidence that religiosity provides moral guidance, emotional resilience, and social support networks that help entrepreneurs navigate stress, ethical dilemmas, and to achieve WLB. This study contributes at three levels: for theoretical to explore new insight and model integrating religiosity into WLB, as for organizational is to explore new mechanism showing how religious values strengthen entrepreneurial practice, and for national, to explore policy implications for fostering ethical entrepreneurship and sustainable work-life integration in Malaysia.